PENGEMBANGAN INSTRUMEN TES MULTIPLE CHOICE HIGH ORDER THINKING PADAPEMBELAJARAN FISIKA BERBASIS E-LEARNING DI SMA - Dian Ratih Utama Sari; Sri Wahyuni; Rayendra Wahyu Bachtiar (FKIP Universitas Jember, 2018)
AbstractThe purpose of this research was to develop and described the validity,reliability, and analysis of items on each test package and know the ability to highorder thinking of the students. The design of this research was 4D development.Based on the results of the analysis and discussion can be concluded that thevalidation results of experts meet the valid criteria. Empirical validity obtained meetthe criteria of validity is very high. Reliability test results on the product indicatethat the category was quite reliable. The item analysis was the difficulty level ofpackets A and B still require improvement. In the item discrimination analysis, therewas 13 problem categories not feasible. In the evaluating item distractor, there was16 questions of packet A and 10 matter of package B with distractor acceptedbecause it is good enough and there are 14 problems with distractor revised. Highorder thinking skill of students after using multiple choice test instrument high orderthimking on e-learning based physics learning in SMA N 1 Glenmore can becategorized quite good .Keyword: multiple choice, e-learning, high order thinking